The Impact of the Covid-19 Pandemic on UMKM in the Tourism Sector in Simalungun Regency - Ngatemin (Politeknik Pariwisata Medan, 2021)
The existence of the Covid 19 pandemic phenomenon that occurred in Indonesia not only attacks factors from health but also has a very serious impact on MSME players in the tourism sector, where UMKM players must immediately make decisions in order to smooth the business economy of MSME products that are traded in the tourism sector in Simalungun Regency. Simalungun Regency as an area that is famous for tourism and culinary objects must be affected, especially for UMKM players. This research uses descriptive research to describe a phenomenon with the theory and results of research that has been done by previous researchers in order to draw conclusions through analysis and scientific methods. Where UMKM players who are affected by the COVID-19 pandemic must limit the products that are sold and some have to close their businesses and switch professions to become farmers and fishermen for economic needs that must be carried out.